Culturally Responsive Traditional Games: A Constructivist Approach to Enhancing Elementary Science Motivation - Ni Luh Anggun Raya Damayanti; Muhammad Aqil; Surahman Wilade; Rizal Rizal; Ryan Andhika Pratama (Journal of Innovation and Research in Primary Education, 2026)
This study investigated the effectiveness of traditional educational games in enhancing learning motivation among fourth-grade students in Natural and Social Sciences (IPAS) instruction. Employing a pre-experimental one-group pretest-posttest design, the research involved 13 students at SD Inpres 2 Balinggi, Central Sulawesi, Indonesia, during the 2025/2026 academic year. Learning motivation was measured using a validated 15-item questionnaire administered before and after implementing traditional game-based instruction on the "Forces Around Us" topic. Data analysis utilized descriptive statistics, Shapiro-Wilk normality testing, and normalized gain (N-Gain) calculations. Results demonstrated consistent improvement across all participants, with mean motivation scores increasing from 66.15 (pretest) to 73.15 (posttest), yielding an N-Gain of 0.79, indicating high pedagogical effectiveness. The uniform 7-point increase, while preventing standard inferential testing due to zero variance, provided compelling evidence of intervention impact. These findings support constructivist frameworks and culturally responsive pedagogy theories, demonstrating that traditional games effectively transform abstract scientific concepts into concrete learning experiences through culturally grounded activities. The study contributes empirical evidence that traditional educational games serve as accessible, low-cost interventions capable of significantly enhancing student motivation in integrated science instruction, particularly valuable for resource-constrained educational settings while challenging deficit perspectives on traditional pedagogical practices.